IOT ENHANCED MONITORING AND ALERT SYSTEM FOR FLOOD AND LANDSLIDE DISASTERS - Dr Shilpa B; Prashant; Amul; Anand; Shreyas (International Educational Journal of Science and Engineering, 2026)
Floods and landslides are some of the most dangerous natural disasters that can cause huge damage to people, property, and the environment. To reduce these risks, this project proposes an IoT-based monitoring and alert system that helps in detecting disaster conditions at an early stage. The system uses different sensors such as water level sensors, rainfall sensors, and soil moisture sensors to collect real-time environmental data from affected areas. The collected data is sent through IoT communication modules like Wi-Fi or GSM to a cloud platform where the data is monitored and Analyzed continuously. Whenever the sensor values cross the safe limit, the system automatically sends warning alerts to nearby people and authorities through SMS, mobile applications, or email notifications. This helps people take quick action before the situation becomes dangerous. The proposed system is simple, low-cost, and suitable for remote areas where continuous manual monitoring is difficult. It also stores previous data for future analysis and improvement of prediction accuracy. By providing real-time monitoring and faster alerts, the system can improve disaster preparedness and help in reducing loss of life and property.